Selective H2S Absorption Using the Mixture of NaOH-NaHCO3-Na2CO3 Buffer Solvent Solution - Anggit Raksajati; Haditya Kukuh Purwanto; Ardian Nugra Baskoro; Antonius Indarto; Danu Ariono (Journal of Engineering and Technological Sciences, 2022)
Acid gas enrichment unit (AGEU) involves selective separation of H2S from acid gas mixture, for example using absorption with an NaOH solvent solution. Sodium carbonate (Na2CO3) and sodium bicarbonate (NaHCO3) buffer addition to NaOH solution suppresses CO2 absorption, thereby increasing the selectivity of H2S absorption. This study evaluated the effect of buffer addition to increase H2S absorption selectivity using an NaOH solution. It was shown that both buffer addition and L/G ratio decrease could increase H2S selectivity by limiting CO2 absorption. Based on the simulation results, in the 0.006 to 0.030 L/G ratio range and NaOH solvent concentration greater than 2%-mass, the addition of NaHCO3 with mass ratio greater than 1.5:1 to NaOH and the addition of Na2CO3 at 1.26 times NaHCO3’s mass increased H2S absorption selectivity up to 17.3%. The combination of an L/G ratio of 0.006 and solvent with a composition of 5%-mass NaOH, 15%-mass NaHCO3, and 18.9%-mass Na2CO3 produced the highest H2S selectivity of 23.1 (379.7% H2S selectivity increase).